2016
DOI: 10.1016/j.freeradbiomed.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide excision repair of oxidised genomic DNA is not a source of urinary 8-oxo-7,8-dihydro-2′-deoxyguanosine

Abstract: Urinary 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodGuo) is a widely measured biomarker of oxidative stress. It has been commonly assumed to be a product of DNA repair, and therefore reflective of DNA oxidation. However, the source of urinary 8-oxodGuo is not understood, although potential confounding contributions from cell turnover and diet have been ruled out. Clearly it is critical to understand the precise biological origins of this important biomarker, so that the target molecule that is oxidised can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…Its precise origin is not fully documented, and diet and cell turnover have been ruled out (Evans et al 2016). The authors could not establish whether 8-oxodG derives from the 2′-deoxyribonucleotide pool, and conclude that: “8-ox-odGuo is most accurately described as a non-invasive biomarker of oxidative stress derived from oxidatively generated damage to 2′-deoxyguanosine.” It should be further noted that for obvious reasons (ease of use and low cost), 8-oxodG in urine is often measured with commercially available ELISA kits and this includes almost all studies mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Its precise origin is not fully documented, and diet and cell turnover have been ruled out (Evans et al 2016). The authors could not establish whether 8-oxodG derives from the 2′-deoxyribonucleotide pool, and conclude that: “8-ox-odGuo is most accurately described as a non-invasive biomarker of oxidative stress derived from oxidatively generated damage to 2′-deoxyguanosine.” It should be further noted that for obvious reasons (ease of use and low cost), 8-oxodG in urine is often measured with commercially available ELISA kits and this includes almost all studies mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it was recently reported that the loss of the Von-Hippel Lindau (VHL) factor, a tumor suppressor and E3 ubiquitin ligase that degrades the hypoxia-inducible factor HIF under normoxic conditions, sensitizes cells to MTH1 inhibition [49]. The unaltered mutagenic burden in MTH1-null mice [28] and the lack of difference in genomic 8-oxodG processing byproducts, such as 8-oxo-7,8-dihydro-2′-deoxyguanosine, in MTH1-null vs. wild-type animals [50] potentially point to redundant mechanisms that can compensate for MTH1 loss. Alternatively, enhanced antioxidant pathways, such as Nrf2 [51], could mitigate the need for MTH1 function by reducing ROS levels and, thus, oxidation in the nucleotide pool.…”
Section: Molecular and Cellular Contexts Underlying The Outcomes Omentioning
confidence: 99%
“…The measurement of 8-oxoG and 8-oxodGuo, which is free of methodological artefactual oxidation, in human and animal fluids by HPLC-MS/MS will not be discussed in detail in this review (for recent reviews, see [111,171,172]. The origin of released 8-oxodG in urine still remains unclear particularly with purines since their metabolism involves enzymatic oxidation [182]. As a final remark, one should note the lack of accurate data on the formation of oxidatively induced damage to 2-deoxyribose in cellular DNA.…”
Section: Measurement Of Oxidatively Generated Damage In Cellular Dnamentioning
confidence: 99%